An integrative literature review of social entrepreneurship research: mapping the literature and future research directions - Klarin, Anton; Suseno, Yuliani (SAGE, 2022)
This article maps existing research from 5,874 scholarly publications on social entrepreneurship (SE) utilizing scientometrics. The mapping indicates a taxonomy of five clusters: (a) the nature of SE, (b) policy implications and employment in relation to SE, (c) SE in communities and health, (d) SE personality traits, and (e) SE education. We complement the scientometric analysis with a systematic literature review of publications on SE in the Financial Times 50 list (FT50) and Business & Society and propose a multistage, multilevel framework that highlights the clusters of existing research on SE based on their stage and level of analysis. This review study also helps outline a set of future research directions, including studies examining (a) the process stage at the micro-level and macro-level, (b) linkages across levels and stages, (c) linkages across stages over time or longitudinal studies, (d) SE in resource-constrained environments, (e) technological advancement and its impact on SE, (f) the types of social enterprises and their outcomes, and (g) various emerging topics in SE.